Estimating Enhanced Endogenous Glucose Production in Intensive Care Unit Patients with Severe Insulin Resistance - Yahia A.; Szlvecz .; Knopp J.L.; Norfiza Abdul Razak N.; Abu Samah A.; Shaw G.; Chase J.G.; Benyo B. (SAGE Publications Inc., 2023)
glucose; glucose; insulin; adult; Article; blood glucose monitoring; cohort analysis; critically ill patient; disease simulation; female; finite element analysis; gluconeogenesis; glucose blood level; glycemic control; human; Hungary; hyperglycemia; hyperinsulinemia; insulin resistance; insulin sensitivity; intensive care unit; major clinical study; Malaysia; male; New Zealand; physiological stress; simulation; critical illness; hyperglycemia; intensive care; intensive care unit; procedures; Blood Glucose; Critical Care; Critical Illness; Glucose; Humans; Hyperglycemia; Insulin; Insulin Resistance; Intensive Care Units